Digital Leadership Strategies to Improve Organizational Performance in the Era of Technological Transformation - Ipang Sasono; Paroli Paroli; Fhia Amelia; Fanani Islamia Ningrum; Michael Ziden (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
Digital transformation has changed the way organizations manage work processes, make decisions, and achieve strategic goals. This study discusses digital leadership strategies to improve organizational performance in the era of technological transformation. The main problems addressed in this study are the low readiness of organizations to adopt digital technology, limited digital competence among leaders and employees, and employee resistance to change. This study uses a qualitative approach with a case study design to explore the role of digital leadership in supporting technology-based business transformation. Data were collected through semi-structured interviews, limited observation, and documentation studies involving organizational leaders, managers, information technology staff, and employees engaged in digital transformation processes. The data were analyzed using thematic coding to identify key themes related to digital leadership strategies, digital culture, technology adoption, employee readiness, and organizational performance. Data validity was strengthened through source triangulation, technique triangulation, and member checking. The findings show that digital leadership plays an important role in building a clear digital vision, improving digital literacy, supporting data driven decision making, encouraging innovation, and creating an adaptive work culture. These strategies can improve operational efficiency, employee productivity, service quality, innovation, and organizational competitiveness. Overall, digital leadership is an important factor in supporting the success of technological transformation and creating sustainable organizational performance.